Carbon emission inventory of a commercial-scale Jatropha (Jatropha curcas L.) biodiesel processing plant - Obligado, Anthony B. (Journal of Environmental Science and Management, 2017)
Biofuel feedstock development is in limelight because of its pronounced capability to reduce greenhouse gas emissions (GHG). The move towards renewable energy intensified research to provide concrete attestations that could be benefited from the effort. This research assessed the GHG reduction potential of biodiesel produced from Jatropha curcas L., relative to that of the conventional petroleum diesel. Computations were based on a standard 30-MLPY biodiesel plant with a co-generation facility, utilizing the byproducts of the process for electricity production. The GHG emissions were standardized and presented as equivalent carbon dioxide emission (CO2e). The boundary set for the analysis was from cradle to grave, considering the life-cycle from the production of the feedstock to the production of biodiesel, and eventually, its end-use. The Life Cycle Assessment (LCA) resulted to a negative net carbon footprint due to the carbon dioxide sequestration capability of the Jatropha plants. The whole system has a net CO2e footprint equivalent to 1,706,365.26 Mg CO2e a-1. Without considering the carbon dioxide absorbed by the plants, LCA of Jatropha biodiesel is still about 25% cleaner than petroleum diesel fuel. With sequestration, the GHG emission reduction can go as high as 548.38%. With the current Philippine biodiesel blending of 2%, if Jatropha methyl ester was used for the blending, this study shows that emission can be cut by 11%. And with increase in the blending, a more positive amount of savings will be achieved, which if at B100, savings could go as high as 581.18%.